Fast methods for jackknifing inequality indices - Lynn A. Karoly; Carsten Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The jackknife is a resampling method that uses subsets of the original database by leaving out one observation at a time from the sample. The paper develops fast algorithms for jackknifing inequality indices with only a few passes through the data. The number of passes is independent of the number of observations. Hence, the method provides an efficient way to obtain standard errors of the estimators even if sample size is large. We apply our method using micro data on individual incomes for Germany and the US.
Keywords: C81; C87; D3; 330; Jackknife; Resampling; Sampling Variability; Inequality